On deoxidation and modification of carbon steel - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It has been shown that the elementary crystal cells of the basic products of deoxidation and modification of carbon steel, δ ferrite and austenite do not correspond to the principle of structural and dimensional correspondence of Dankov – Konobeevsky. Modifying elements Ba, Ca, Mg, Ce, Al increase the surface energy of the iron‑carbonaceous melt by binding surface active oxygen. Deoxidizers combine dissolved (free) oxygen into oxides, and modifiers – adsorbed oxygen. Steel modification is a nanostructural process in which modifying elements refine elemental iron nanocrystals from adsorbed oxygen and hydrogen atoms. Modifying elements reduce the concentration of dissolved hydrogen, which contributes to the modifying effect. The strongest deoxidizer and modifier of carbon steel is magnesium.